EFEKTIVITAS PENYELENGGARAAN PROGRAM PELATIHAN KERJA DALAM MENINGKATKAN KOMPETENSI KERJA - Adela Anita; Asep Saepudin; Iip Saripah (Jurnal Dedikasi Pendidikan, 2024)
: One of the roles of training to improve the quality of human resources is through skill/skill development activities or what is called life skills education. Job training is an important means of developing human resources. The development of this workforce is expected to later become a workforce that is ready to use, in the sense that it can immediately enter the world of work. The orientation of the job training program is very necessary considering that most of the labor force in Indonesia still works in the informal sector with very low productivity. Competence is the work ability that a person has to carry out his work in accordance with existing standards accompanied by aspects that follow it (knowledge, understanding, skills, values, attitudes, interests). The effectiveness of the implementation of work training programs in improving work competence. To obtain satisfactory results from the existence of job training programs is determined by a predetermined plan, namely the monitoring process after job training. The monitoring stage intends to determine the suitability and suitability of the program of activities carried out with the plans that have been prepared. This stage is used to correct activities that are not in accordance with the plan, correct the abuse of rules and resources, and seek to achieve the specified goals as efficiently and effectively as possible for the future. Collection of data or information in monitoring activities to see conditions on the ground in the implementation of the training program that is being monitored..